2009
DOI: 10.1186/1745-6150-4-27
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of life in the Zinc world. 2. Validation of the hypothesis on the photosynthesizing zinc sulfide edifices as cradles of life on Earth

Abstract: Background: The accompanying article (A.Y. Mulkidjanian, Biology Direct 4:26) puts forward a detailed hypothesis on the role of zinc sulfide (ZnS) in the origin of life on Earth. The hypothesis suggests that life emerged within compartmentalized, photosynthesizing ZnS formations of hydrothermal origin (the Zn world), assembled in sub-aerial settings on the surface of the primeval Earth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
85
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 338 publications
3
85
1
Order By: Relevance
“…A recent paper in PNAS (1) analyzed the evolution of metalloproteins and confirmed our earlier observation on the abundance of Zn-binding proteins among the most widespread-and evolutionarily oldest-protein folds (2). Because that observation seemed to contradict the extremely low (<10 −12 M) estimates of Zn levels in the primeval anoxic ocean (3), we had suggested that the first cells developed in continental Zn-rich environments (2,4).…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…A recent paper in PNAS (1) analyzed the evolution of metalloproteins and confirmed our earlier observation on the abundance of Zn-binding proteins among the most widespread-and evolutionarily oldest-protein folds (2). Because that observation seemed to contradict the extremely low (<10 −12 M) estimates of Zn levels in the primeval anoxic ocean (3), we had suggested that the first cells developed in continental Zn-rich environments (2,4).…”
mentioning
confidence: 52%
“…Because that observation seemed to contradict the extremely low (<10 −12 M) estimates of Zn levels in the primeval anoxic ocean (3), we had suggested that the first cells developed in continental Zn-rich environments (2,4). Specifically, we proposed that hydrothermal precipitates of zinc sulfide (ZnS), similar to those seen at modern deep sea vents, catalyzed abiogenic photosynthesis of organic compounds under the solar light (2,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mulkidjanian and Galperin suggested that the Zn-binding proteins and RNA structures found in all of modern life must have been present in the last universal common ancestor (41). Invoking the hypothesized Zn concentrations in the Archean ocean (9), they concluded that the last universal common ancestor must have evolved near metal-rich hydrothermal vents (41).…”
Section: Emergence Of the Akaryotes Metal Homeostasis And Biogeochementioning
confidence: 99%
“…The principle of chemistry conservation can be used as an additional major constraint for reconstructing primordial environmental conditions in the absence of reliable geological record. For example, ancient, ubiquitous proteins often use Zn and Mn, but not Fe, as transition metal cofactors; this preference is retained across the three domains of life (12). The abundance of Zn-and Mn-dependent enzymes during the earliest steps of evolution and the later recruitment of Fe has been inferred also from a global phylogenomic reconstruction (13).…”
mentioning
confidence: 99%